Effect of firing temperature on the microstructure and performance of PrBaCo2O5+d cathodes on Sm0.2Ce0.8O1.9 electrolytes fabricated by spray deposition-firing processes - Chen, D.; Ran, R.; Shao, Zongping (Elsevier SA, 2010)
The effect of firing temperature on the microstructure and performance of PrBaCo2O5+d cathodes on Sm0.2Ce0.8O1.9 electrolytes fabricated by spray deposition-firing processes is systematically studied by various characterization techniques. The grain size, porosity and particle connection of the electrode as well as the physical contact between the PrBaCo2O5+d and Sm0.2Ce0.8O1.9 layers are influenced differently by the firing temperature. The area specific resistances (ASRs) of the various PrBaCo2O5+d cathodes are measured by electrochemical impedance spectroscopy in both symmetrical two-electrode and three-electrode configurations. The lowest ASR and cathode overpotential are achieved at a firing temperature of 1000 °C. Two main oxygen reduction reaction processes are proposed according to the oxygen partial pressure dependence of the electrode ASR. The rate-determining step is transmitted from a charge-transfer process at low firing temperatures to a non-charge-transfer process at high firing temperatures. A fuel cell with the PrBaCo2O5+d cathode fired at an optimal temperature of 1000 °C delivers the attractive peak power density of 835 mW cm-2 at 650 °C, while this density is much lower for other firing temperatures. This result suggests the firing temperature of PrBaCo2O5+d electrodes should be carefully optimized for practical applications. © 2010 Elsevier B.V. All rights reserved.